ANALISIS SIMBOLIS PADA KARYA SASTRA DALAM MODUL AJAR BAHASA INDONESIA SMA KELAS X: KAJIAN SEMIOTIKA ROLAND BARTHES - Nurhalimah; Ari Kartini; Zoni Sulaiman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the fact that many students in literature learning only understand the text in its literal meaning. Thus, this research can make learning materials more effective and help in achieving the objectives of the Independent Curriculum. The data are in the form of short story excerpts and lines of poetry in the Indonesian language teaching module for senior high school class: X. This study aims: 1) to determine how the forms of denotative and connotative meanings that appear in literary works of short stories and poetry in the Indonesian language teaching module for class: X of the independent curriculum are based on Roland Barthes' semiotic theory, 2) to determine how the construction of symbolic meaning in literary works of short stories and poetry in the Indonesian language teaching module for class: X of the independent curriculum, and 3) to determine how the construction of myths in literary works of short stories and poetry in the Indonesian language teaching module for class: X of the independent curriculum. The research method uses descriptive qualitative, with data collection through documentation studies. The research results revealed that the analysis of symbolic, denotative, and connotative meanings, as well as myths, in short stories and poems included in the Indonesian language teaching module for senior high school grade X found 85 data points. This indicates the presence of symbolic, denotative, and connotative meanings, as well as myths, in 20 data points from short stories and 65 points from poems. Based on the analysis of short stories and poems, the researchers concluded that this study expands Roland Barthes's semiotics by applying it to pure literary works such as short stories and poems in the Indonesian Language Teaching Module for Grade X of the Merdeka Curriculum. Therefore, the results can contribute to the development of teaching materials in schools.